2011
DOI: 10.1111/j.1528-1167.2010.02970.x
|View full text |Cite
|
Sign up to set email alerts
|

An association analysis at 2q36 reveals a new candidate susceptibility gene for juvenile absence epilepsy and/or absence seizures associated with generalized tonic-clonic seizures

Abstract: Summary Purpose:  To further evaluate the previously shown linkage of absence epilepsy (AE) to 2q36, both in human and WAG/Rij absence rat models, a 160‐kb region at 2q36 containing eight genes with expressions in the brain was targeted in a case–control association study involving 205 Turkish patients with AE and 219 controls. Methods:  Haplotype block and case–control association analysis was carried out using HAPLOVIEW 4.0 and inhibin alpha subunit (INHA) gene analysis by DNA sequencing. Key Findings:  An a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Sander et al reported an allelic association with GLU R5 kainate receptor gene (GRIK1 polymorphism), which has a role in excitatory neurotransmission [ 81 ]. Another association study revealed a strong association of a common intronic SNP (rs7588807) in the inhibin alpha precursor gene (INHA) with JAE [ 113 ]. INHA encodes inhibin protein, which inhibits the secretion of follicle-stimulating hormone (FSH), in turn inducing the production of progesterone and estradiol.…”
Section: Genetic Studies Of Common Epilepsiesmentioning
confidence: 99%
“…Sander et al reported an allelic association with GLU R5 kainate receptor gene (GRIK1 polymorphism), which has a role in excitatory neurotransmission [ 81 ]. Another association study revealed a strong association of a common intronic SNP (rs7588807) in the inhibin alpha precursor gene (INHA) with JAE [ 113 ]. INHA encodes inhibin protein, which inhibits the secretion of follicle-stimulating hormone (FSH), in turn inducing the production of progesterone and estradiol.…”
Section: Genetic Studies Of Common Epilepsiesmentioning
confidence: 99%
“…An association study with 205 Turkish IAE patients revealed a strong association of a common SNP (rs7588807) in the inhibin alpha precursor gene (INHA) in 2q36 to JAE and/or to IAE with GTCS. 76 The INHA gene has also been screened through DNA analysis and three potentially damaging mutations have been identified. Inhibin protein, commonly known as a gonadal glycoprotein, inhibits the secretion of follicle-stimulating hormone which in turn induces the production of progesterone and estradiol.…”
Section: Non-ion Channel Genesmentioning
confidence: 99%
“… 4 AEs are often studied apart, but some investigations show common genetic causality, 5 whereas others identify factors that are not shared. 6 Recurrent microdeletions at 15q11.2, 15q13.3, and 16p13.11 are strongly associated risk factors for GGEs, occurring in 0.5% to 1% of patients. 7 Around 8% of patients with GGE also carry rare gene-disrupting copy number variations (CNVs), with enrichment for genes previously implicated in neurodevelopmental disorders, including deletions of RBFOX1 and NRXN1 .…”
mentioning
confidence: 99%